Mathematical model applied to the control of carbon in pulp process - Pérez-Matos, Edgar Ademar (2023)
The mathematical relationships obtained denote the complexity of the operation in the leached and adsorbed gold stage on activated carbon; since significant losses of gold in solution occur in real metallurgical operations. Similarly, in the adsorbed gold operation, it reveals its high kinetics at the beginning and tends to decrease as the process progresses; eventually reaching the maximum gold load that the carbon can accommodate, and then showing the opposite trend. Furthermore, varying the concentration of carbon affects the adsorption operation; that is, the kinetics of gold adsorbed on carbon decreases over time, but the operation has higher kinetics with a larger volume of carbon during adsorption. The mentioned aspects are made possible by establishing the respective mathematical model of gold in barren solution and gold loaded on carbon; then optimizing with Solver - an Excel tool - the two parameters, such as the loading capacity and the kinetic constant of activated carbon, both closely linked to the process; with the condition of obtaining a lower relative error and, consequently, a higher degree of confidence. This allows us to closely resemble the mathematical model to reality, accurately predicting the operation of gold adsorption on carbon, while varying the flow rate in the adsorption process.